Scepticism and Faith in the Philosophy of Pascal - Wilde, Norman (1916)
The neglect of Pascal by the English-speaking world today is little short of amazing. Within the last decade France has produced literally scores of studies of his life and thought; but, with the exception of a book by St. Cyres and an essay by Paul Elmer More, there has been scarcely a sign that we were conscious of any special relation between the spirit of our own age and that of this seventeenth-century genius. Yet Pascal is indeed a man of the present, and a study of his multiplex personality has never been more pertinent than it is today. Geometrician, experimental physicist, biting satirist, literary artist, keen-sighted moralist, devout believer, philosophical sceptic, man of the world, ascetic recluse, the problem of the balance and inter-relation of these selves is still waiting a completely satisfactory solution. How was it that the geometrician and experimental physicist could be a pronounced supernaturalist? How was it that the almost cynical man of the world could become the devout recluse? What relation can we find between the sceptical doubt of the possibility of knowledge and the obedient acceptance of the dogmas of the church? With what consistency could the rationalistic critic of Jesuit morality be the challenger of all philosophic creeds? How could all these conflicting interests keep house together in the same frail tenement and present the semblance of a unified life? Perhaps they could not, and his death in his fortieth year was the outcome.